The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/16549716.2017.1298890
|View full text |Cite
|
Sign up to set email alerts
|

Production and use of estimates for monitoring progress in the health sector: the case of Bangladesh

Abstract: Background: In order to support the progress towards the post-2015 development agenda for the health sector, the importance of high-quality and timely estimates has become evident both globally and at the country level. Objective and Methods: Based on desk review, key informant interviews and expert panel discussions, the paper critically reviews health estimates from both the local (i.e. nationally generated information by the government and other agencies) and the global sources (which are mostly modeled or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 10 publications
(11 reference statements)
0
20
0
Order By: Relevance
“…Because the DGFP MIS is not connected to DHIS2, data collected under the DGFP cannot be accessed and analyzed with DHIS2. This lack of synchronization creates parallel reporting systems (40) . The study participants highlighted this duplicity in reporting and mentioned the di culty of managing multiple forms and reporting the same RMNCAH indicators in different formats for different stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Because the DGFP MIS is not connected to DHIS2, data collected under the DGFP cannot be accessed and analyzed with DHIS2. This lack of synchronization creates parallel reporting systems (40) . The study participants highlighted this duplicity in reporting and mentioned the di culty of managing multiple forms and reporting the same RMNCAH indicators in different formats for different stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Like China, the health information management systems in many low-and middle-income countries are fragmented and often include multiple vertical systems designed to meet the requirements of the national government or international organizations/donors. As a result, similar problems occur in other low and middle-income countries (2,17,(22)(23)(24)(25)(26)(27)30). For example, in Indonesia, the reporting forms in each health center are different, which results in missing data and hampers the data standardization process (2,17,30).…”
Section: Discussionmentioning
confidence: 98%
“…Research on Indonesia found that its private health sector hardly reports TB cases, as required by its national health legislation (22). Similarly, there is also evidence that India, Namibia, and Thailand all suffer from a lack of national data standardization and accessibility (22)(23)(24)(25)(26)(27)(28), and might not accurately report the number of confirmed TB cases. It is also reasonable to assume that many other low-and middle-income countries without high functioning health information management systems could face similar problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations